2018
DOI: 10.3390/su10072357
|View full text |Cite
|
Sign up to set email alerts
|

Location Recommendation of Digital Signage Based on Multi-Source Information Fusion

Abstract: Abstract:With the increasing amount of digital signage and the complexity of digital signage services, the problem of introducing precise location recommendation methods for digital signage should be solved by digital signage enterprises. This research aims to provide a sustainable location recommendation model that integrates the spatial characteristics of geographic locations and multi-source feature data to recommend locations for digital signage. We used the outdoor commercial digital signage within the Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Beijing is an important city where the global digital signage industry gathers. In central Beijing and its suburbs, digital signage accounts for 85% of the total signage in Beijing [20]. The 2014 Beijing Population Sample Survey Report showed that 79.5% of Beijing's permanent population is concentrated within the Sixth Ring Road [40].…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Beijing is an important city where the global digital signage industry gathers. In central Beijing and its suburbs, digital signage accounts for 85% of the total signage in Beijing [20]. The 2014 Beijing Population Sample Survey Report showed that 79.5% of Beijing's permanent population is concentrated within the Sixth Ring Road [40].…”
Section: Study Areamentioning
confidence: 99%
“…Sheppard et al [16] used voice input and natural language processing methods to implement digital signage in the form of voice forwarding, enabling users to find information faster than with standard touch-screen-only methods. In addition, emerging technologies represented by big data technology have promoted the development of intelligent platforms for digital signage terminal management, automatic scheduling, and content distribution [17][18][19][20]. In summary, the research on digital signage mainly focuses on consumption behaviour and information system construction and lacks the site selection of digital signage.…”
Section: Introductionmentioning
confidence: 99%
“…The core urban built-up area is mostly covered within the Sixth Ring Road in Beijing, and has a large number of commercial and entertainment centers, government agencies, hospitals, universities and other urban facilities. Extensive digital signage highly distributed in the region, accounting for 85% of the total amount of digital signage in Beijing [16].…”
Section: Study Area and Data Sourcementioning
confidence: 99%
“…The layout of digital signage and its advertising effects are constrained by the location, accessibility, visibility, and the geographical environment surrounding the signage, which are decisive for the scientific management of digital signage [32]. Moreover, in former researches, the commercial activity, traffic capacity, population and the housing price were used as the environmental factors in this field [16,32]. In addition, we used the data of the number of commercial workers, the traffic network centrality index, the check-ins data, and the average house price to represent these factors.…”
Section: Study Area and Data Sourcementioning
confidence: 99%
See 1 more Smart Citation